The age of bioinspired molybdenum‐involved nanozymes: Synthesis, catalytic mechanisms, and biomedical applications. Issue 3 (1st February 2021) - Zu, Yan; Yao, Huiqin; Wang, Yifan; Yan, Liang; Gu, Zhanjun; Chen, Chunying; Gao, Lizeng; Yin, Wenyan
Abstract: Molybdenum (Mo), as a nontoxic and low‐cost transition metal, has been employed for synthesis of various Mo‐based nanomaterials with unique structures and physicochemical features to achieve various properties. Especially, bioinspired Mo‐based nanomaterials show great potential for the construction of novel nanozyme catalysts due to their variable oxidation states. Overcoming drawbacks of natural enzymes, bioinspired Mo‐based nanozymes not only provide effective catalytic sites or multivalent elements to mimic natural enzymes, but also present multiple functions for interfacing with various biomicroenvironments. Construction of vast Mo‐based nanozymes has attracted enormous interest in biomedicine. Exogenous/endogenous stimuli enable the user to tailor the catalytic activities of Mo‐based nanozymes. Additionally, tunable physicochemical properties also have a significant influence on their enzyme‐like activity. In this review, we comprehensively summarize typical synthesis strategies, catalytic mechanism, and types of enzyme‐like activity of the bioinspired Mo‐based nanozymes. We mainly highlight desired merits of bioinspired Mo‐based nanozymes related to tunable enzyme‐like activity, stability, and multifunctionality through regulating their physicochemical properties. Furthermore, we intend to discuss their biomedical applications in biosensing and detection, oncotherapy, and combating bacteria. Finally, current challenges and future perspectives of the Mo‐based nanozymes are also proposed. Abstract : Mo‐based nanomaterials have shown great potential for the construction of novel nanozyme catalysts due to their variable oxidation states. Overcoming drawbacks of natural enzymes, Mo‐based nanozymes not only provide effective catalytic sites or multivalent elements to mimic natural enzymes, but also present multiple functions for interfacing with various biomicroenvironments. In this review, we summarize recent advances in synthesis, catalytic mechanisms, and biomedical applications of Mo‐based nanozymes and discuss the challenges and future prospects in this booming field.